Revitalisasi Pendidikan Agama Islam dalam Menjawab Tantangan Era Society 5.0 - Hasriyanti Mandalika Hasan; Amaluddin Amaluddin (Journal of Humanities, Social Sciences, and Education, 2025)
The Society 5.0 era is a new phase of civilization that places technology at the center of human life without ignoring human values. In this context, Islamic Religious Education (PAI) faces complex challenges, ranging from moral crises, information disruption, to the erosion of spiritual values. This study aims to critically analyze how PAI revitalization can be the answer to these challenges through a literature study approach. By reviewing various recent academic sources, this study highlights the importance of curriculum transformation, technology integration, value-based learning, strengthening student character, and the adaptive role of teachers. The results of the analysis show that PAI must be more contextual and responsive to changes in the times, while maintaining the substance of Islamic teachings which are rahmatan lil 'alamin. Revitalization is not merely cosmetic, but includes a change in the educational paradigm towards a more humanistic and transformative direction. Islamic Religious Education needs to be oriented towards the formation of spiritual character, digital ethics, and critical thinking skills that can guide the younger generation in facing the complex digital era. Thus, PAI becomes the vanguard in producing a religious generation that excels intellectually, emotionally, and spiritually in the Society 5.0 era.